Pengaruh Empowerment dan Pelatihan terhadap Kinerja Karyawan pada Wyndham Tamansari Jivva Resort Bali - Putri, Ni Putu Rika Loistiana; Ayu Wimba, I Gusti; Gede, I Komang (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2024)
This research was conducted at Wyndham Tamansari Jivva Resort Bali. The population in this study is employees at Wydham Tamansari Jivva Resort Bali which amounts to 100 employees using saturated sampling techniques which means all members of the population are involved as research subjects. Data collection was carried out by observation, interviews, documentation, literature studies, and questionnaires measured using the Linkert Scale of five answer choices ranging from strongly disagsreeing with the value of one to the value of strongly agreeing with the value of five.Instrument tests are carried out with validity tests and reliability tests using SPSS software. The data analysis techniques used  are classical assumption tests, multiple linear analysis, coefficient of determination analysis and significant tests (t test and f test). The results of the analysis show that empowerment has a positive and significant effect on employee performance, training has a positive and significant effect on employee performance, empowerment and training simultaneously have a positive and significant effect on employee performance